ANALISIS AMAR MAKRUF NAHI MUNGKAR DALAM HR MUSLIM:78 PERSPEKTIF AL-GHAZALI - Faida, Farah; Makky, Alfanul (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2023)
Amar makruf nahi mungkar is obligated to teach Islam. Al-Ghazali is one of the Islamic salaf scholars who conceptualized amar makruf nahi munkar in exact details. For this reason, this study was aimed to describe Al-Ghazali's point of view regarding amar makruf nahi mungkar in the book of Ihyā’ī ‘Ulūm Ad-Dīn, especially regarding the stages of amar makruf nahi mungkar and the concept of its formulation by looking at the substance of Hadith narrated by Muslim: 78. This study was conducted using a library research method using a qualitative approach. The result showed that Al-Ghazali had his view that amar makruf and nahi munkar are actually one term with the same object and the same goal. Amar makruf nahi mungkar had also three ethics to be fulfilled i.e. knowledge, wara', and ḥusn al-khulq. Al-Ghazali had also owned a concept about the stages of amar makruf nahi mungkar that are in accordance with fiqh rules. This concept does not conflict with the content of the hadith narrated by Muslim: 78.